Macroinvertebrate assemblages in Gorgona Island streams: spatial patterns during two contrasting hydrologic periods - Gómez-Aguirre, Ana M.; Longo-Sánchez, Magnolia C.; Blanco, Juan F. (Actualidades Biológicas, 2012)
Studies comparing various streams are scarce in tropical insular systems and inexistent in Colombia. In order to understand the spatial patterns of macroinvertebrates in tropical insular streams, and the environmental drivers of such patterns, we tested for patterns among streams but using a nested sampling design from streams to microhabitats in Gorgona Island (Colombia, Tropical Eastern Pacific) during two seasons (low and high precipitation). We found that benthic macroinvertebrate assemblages showed clear differences among streams despite of the variability within nested levels. Hydrologic disturbance tended to homogenize spatial patterns in most of the streams. Although ordinations of sampling units using either macroinvertebrate composition or environmental variables were not fully consistent, it was evident that water physicochemistry influenced by underlying geology was a pervasive driver of macroinvertebrate distribution. We highlight the importance of incorporating multiscale sampling designs for studying distributions of macroinvertebrates in tropical islands, and for biomonitoring.